Feasibility of waste-derived hydroxyapatite mixed with ultra high molecular weight polyethylene composites for fused deposition modeling process - Md Ansari, Mohamad Helmi (2018)
In this study, feasibility of waste-derived hydroxyapatite (HAp) reinforced UHMWPE composites for Fused Deposition Modeling (FDM) process was investigated. Compared to the commercial HAp, derived from natural resources such as corals, fish bone and eggshells have been converted into HAp and show the similarity with the commercial HAp. Ca/P ratio was so important to human body because Ca influence growth of human bones and P play a role in immune system activation. This research has used waste eggshell has been used to synthesize HAp by using hydrothermal synthesis. The Ca/P ratio was investigated by using SEM/EDS and XRD test. By using these test, it revealed Ca/P ratio of waste-derived HAp has shown 1.69 approximately with the standard Ca/P ratio (1.67). HAp/UHMWPE composites formulation samples were prepared by mixed between HAp and UHMWPE using Brabender Mixer. HAp/UHMWPE composite formulation samples were characterized by their weight percentage. The feasibility of each HAp/UHMWPE composite samples has been studied by their morphology, thermal and rheology properties by using SEM/EDS, TGA/DSC and Rheology test. Formulation sample U50H50 with 50 wt.% of HAp has shown the homogenous mixture, 1.69 Ca/P ratio, lowest melting point and good pseudo-plastic behavior compared to other formulation samples. Therefore, this formulation samples has been used in single screw extruder to fabricate diameter size of 1.75+0.05 mm filament wire for FDM process. DOE has been developed by using Taguchi method with the parameter controlled were die temperature and screw frequency. The optimum parameter setting to produce the diameter of 1.75+0.05 mm filament wire was successfully found at screw frequency of 2.5 Hz and die temperature of 190 ºC. The characteristic of the FDM process shows the samples with optimum dimensional accuracy and relative density was found at 245 ºC of temperature nozzle and 130 ºC of temperature platform. This result shown Hap/UHMWPE composite has potential to become material filament wire feedstock for FDM process.